Letter from Rosa Bredig to Max Bredig, May 30, 1927 - Bredig, Rosa (1927)
Rosa Bredig (1877-1933) gives her son, Max Bredig (1902-1977), advice regarding his future and suggests that he take better care of his well-being with nutritious food and exercise. She also looks forward to his visit at Pentecost and suggests that he let his father, Georg Bredig (1868-1944), help him financially.
Keywords: Bredig, Max Albert, 1902-1977; Bredig, Rosa, 1877-1933